Lockridge family histories: looking for the raintree. Issue 1 (2nd January 2017) - Sandweiss, Eric
Abstract: Novelist Ross Lockridge, Jr., killed himself months after the publication of his highly publicized novel, Raintree County . Why? This article seeks an answer in the writer's conflicted relationship to History: of his country, of his family (including his father, the best-known historian in his home state of Indiana), of his own grand ambitions. Lockridge had crafted a fictional hero, Johnny Shawnessy, who sought to 'hear the words before the words become History.' For the writer himself – and, subsequently, for his children, who carry on the family quest to reveal historical truth – History has proved a harder burden to overcome.